The macroeconomic effects of global supply chain reorientation - Daragh Clancy; Donal Smith; Vilém Valenta (European Central Bank (ECB), 2024)
Policymakers around the world are encouraging the local production of key inputs to reduce risks from excessive dependencies on foreign suppliers. We analyse the macroeconomic effects of supply chain reorientation through localisation policies, using a global dynamic general equilibrium model. We proxy non-tariff measures, such as the stricter enforcement of regulatory standards, which reduce import quantity but do not directly alter costs and prices. These measures have, so far, been a key component of attempts to reshore production and are an increasingly popular trade policy instrument in general. Focusing on the euro area, we find that localisation policies are inflationary, imply transition costs and generally have a negative long-run effect on aggregate domestic output. The size (and sign) of the impact depends on whether these policies are implemented unilaterally or induce a retaliation from trade partners, and also the extent to which they reduce domestic competition and productivity. We provide some recommendations for policymakers considering implementing a localisation agenda.
Keywords: F13; F41; F45; F62; 330; General equilibrium; Reshoring; Strategic autonomy